Views on the transregional interaction in Iberian Southwest Recent Prehistory: questioning the shells and molluscs from Perdigões. - Valera, António Carlos (2017)
In face of an insufficient research of the circulation and consumption of molluscs and shells in transregional interaction networks, the present paper questions the presence of these faunal remains in the ditched enclosures of Perdigões, not in terms of subsistence (in this case irrelevant), but rather in an ideological perspective of consumption in the context of the social role played by exogenous products in large aggregation centres of inner Alentejo region. An inventory and taxonomic classification are presented and a diachronic and contextual analyses is developed, highlighting the scarce, but growing, consume of molluscs and the importance conceded to the use of some shells, underlining the preponderance of the imported material. The comparing with other regional available collections shows the specific character that these faunal remains may represent in Perdigões in the context of the interregional network integrated by this site. Keywords: Ditched enclosures, Interaction, Molluscs, Recent Prehistory, Shells.